THE IMPORTANCE OF THE UTILIZATION OF FOREST FRUITS IN BATAK TOBA COMMUNITY - Alfonsus H Harianja; Anisse M. Sinaga; Ferry A Hawari; Ridwan Fauzi (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2021)
Batak Toba community who live in the surrounding forests utilise forest-fruits that grow around their settlement. This research aims to describe the important value of the forest fruits using the Local Users Value Index (LUVI) assessment as most of the fruits have not yet been traded. The research was conducted in Simardangiang and Sitoluama Villages in North Tapanuli Regency, 2015. Data collection was done by interviewing 65 respondents selected purposively based on gender and age classification. The results showed that there were 29 species of forest fruits utilised by the community. They were categorised into four utilisation types: fresh fruit, flavouring fruit, processed fruit, and medicines. In Simardangiang Village, the five most important fruits were kapundung or menteng (Baccaurea racemose) (0.56), hopong (Macaranga lowii) (0.52), sotul, santol or sentul (Sandoricum koetjape) (0.48), harimonting or kemunting (Rhodomyrtus tomentosa) (0.47), and habo or kabau (Archidendron bubalinum) (0.42). Meanwhile, in Sitoluama Village, the five most important fruits were kapundung (Baccaurea racemosa) (0.50), hopong (Macaranga lowii) (0.41), sihim or rotan manau (Calamus manan) (0.32), handis or gamboge (Garcinia xanthochymus) (0.32), and mobe (Artocarpus dadah) (0.19). The numbers in parentheses are the important value based on LUVI. The forest fruits that have domestication potency are kapundung (Baccaurea racemose), hopong (Macaranga Iowii), sihim (Calamus manan), handis (Garcinia xanthochymus), mobe (Artocarpus dadah), harimonting (Rhodomyrtus tomentosa), sotul (Sandorium koetjape) and habo (Archidendron bubalinum).